(untitled) (PerCursos, 2023)
In Northern Mozambique, there is a coexistence between the state and tradition that allows for the cohabitation of different metaphysics, which in turn lead to differences regarding the right to use the land. While according to the Mozambican legal system land belongs to the state and is not available for private ownership, for tradition, every piece of land has its owner, reflecting the significance of the connection between the land and the ancestral spirits inhabiting it. This traditional dynamic is to be followed by all, including foreign companies and investors seeking to exploit the territory and its natural resources. The objective of this article is to present, through ethnographic examples, some of the controversies and cosmological agreements that revolve around the relationship between exploitative foreign capital and the politics of the visible and invisible realms.